The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1515/opag-2022-0137
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield stability of black soybean lines across three agroecosystems in West Java, Indonesia

Abstract: Black soybean (Glycine soja (L.) Merril) is one of the potential agricultural commodities in Indonesia. The multilocation trial is the primary requirement for variety release before farmers can widely use the new varieties. Various stability measurements on grain yields will provide more accurate information in selecting superior lines. The aims of the study were to: (i) identify the effect of genotype by environment interactions (G×E) on black soybean grain yields; (ii) select the black soybean lines with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The effect of GEIs decreases the relationship between genotype and phenotypic values, and also makes it difficult for breeders to select superior genotypes [ [6] , [7] , [8] ]. Therefore, interpreting GEIs in multilocation tests is very helpful in determining the stability of genotypes in diverse environments, or adaptive to specific environments [ [8] , [9] , [10] , [11] ]. Numerous methods have been suggested to analyze GEIs, adaptability and stability of genotypes under diverse environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of GEIs decreases the relationship between genotype and phenotypic values, and also makes it difficult for breeders to select superior genotypes [ [6] , [7] , [8] ]. Therefore, interpreting GEIs in multilocation tests is very helpful in determining the stability of genotypes in diverse environments, or adaptive to specific environments [ [8] , [9] , [10] , [11] ]. Numerous methods have been suggested to analyze GEIs, adaptability and stability of genotypes under diverse environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, GEIs make the selection process difficult and inefficient under various environmental conditions [7,13,14]. Several studies have reported that GEIs complicate the selection process in sweet potatoes [7,15], durum wheat [16], soybeans [17][18][19], maize [20], Stevia [21], and turmeric [22]. Therefore, a study is needed to evaluate Fe-resistant rice genotypes under a wide range of environmental conditions to obtain superior genotypes (high and stable yields).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Karuniawan et al, [31] used numerical measurements, AMMI, and GGE biplot to select stable sweet potatoes in West Java, Indonesia. Several other studies also reported the relative contribution of these various measurements to identify the ideal line, including on barley [43], on maize [44,45], on safower [46], on stevia [47], and soybean [48,49]. From our test results, there were four new soybean lines that were identifed as stable and highyielding by various stability measurements, namely A-5A-PSJ (S2), DB-96-CTY (S5), UP 161 (S6), and UP 162 (S7).…”
Section: Discussionmentioning
confidence: 99%